PEKERJAAN RAMAH LINGKUNGAN DI INDSUTRI HOSPITALITY: SUATU TINJAUAN - Irene Hanna H. Sihombing; Ni Made Suastini (Bogor Hospitality Journal, 2023)
The growing importance of sustainability in the hospitality industry stems from the recognition of its impact on the environment, society, and the long-term viability of the industry itself. The hospitality industry is resource-intensive and can have a significant ecological footprint. However, there seems to be a gap in literature specifically addressing the concept of green jobs within the context of the hospitality industry. This study utilizes academic databases, such as PubMed, ResearchGate, and ScienceDirect, to search for relevant articles, research papers, and reports. The literatures was categorized based on themes, such as job creation, training and skills development, environmental impact, and economic benefits. The research findings reveal that there is currently no specific study on green jobs in the hospitality industry. This is because the industry does not yet have a significant number of green jobs, environmental policies, or the production and provision of green products or services. This research could contribute to understanding the challenges, opportunities, and best practices related to green jobs in the sector.